Characterisation of Bioactive Compounds and In Vitro Anticancer and Anthelmintic Activities of Ilex khasiana, an Endangered Species of Holly From Mizoram, India - Charles Lalnunfela; P. B. Lalthanpuii; H. T. Lalremsanga; null Zothansiama; C. Lalmuansangi; N. Senthil Kumar; T. C. Lalhriatpuii; Kholhring Lalchhandama (Scientifica)
Ilex khasiana Purkay. is a critically endangered species of holly found only in Khasi Hills and Mizoram, Northeast India. Of its several medicinal uses in the Khasi and Mizo traditional systems, the anticancer and anthelmintic applications remain unexplored. A methanol extract (IKM) and three fractions, namely, butanol (IKM-B), diethyl ether (IKM-D) and hexane (IKM-H) extracts were prepared from the leaves. Cytotoxicity tests were performed in vitro on malignant human alveolar adenocarcinoma (A549) and human colorectal carcinoma (HCT116) cell lines using the 3-(4,5-dimethylthiazol-2-yl)-2,5 diphenyltetrazolium bromide (MTT) reduction reaction. All the extracts exerted inhibitory efficacy in the order, IKM-D > IKM-B > IKM > IKM-H. IKM-D was the most efficacious extract exhibiting the half-maximal inhibitory concentration (IC50) values of 26.9, 64.04 and 28.61 μg/mL against A549 cells, and 22.77, 69.41 and 18.37 μg/mL against HCT116 cells at 24, 48 and 72 h, respectively. The most bioactive extract, IKM-D, was used for further anticancer tests. It induced apoptosis as indicated by red fluorescence in the dead cells. The apoptotic index values were determined at 33.5, 55.18 and 57.62 in A549 cells, and 32.47, 54.29 and 62.55 in HCT166 cells at the corresponding concentrations of 25, 50 and 100 μg/mL. It also caused significant clonogenicity by repressing cancer proliferation, but only at a concentration of 100 μg/mL. Surviving fractions of the cancer cells following extract treatment at 25, 50 and 100 μg/mL were 52.16%, 47.56% and 21.77% for A549 cells, and 52.56%, 48.12% and 8.42% for HCT116 cells. The plant extract also caused concentration-dependent inhibition of colony formation against both cell lines. Anthelmintic activity was demonstrated in an intestinal cestode, Raillietina galli. Scanning electron microscopy revealed hallmark anthelmintic alterations on the body parts of the parasite. The GC-MS analysis showed that the plant extract is mainly composed of a phenol, 2,6-di-tert-butylphenol. High-performance thin-layer chromatography (HPTLC) fingerprinting and quantification indicated the presence of β-sitosterol at an amount of 198.68 ng. The two compounds were predicted by computational modelling to have high binding potentiality on β-tubulin, a common anticancer and anthelmintic target. The findings established that I. khasiana leaves contain bioactive principles that caused inhibitory effects on carcinoma cells and produced anthelmintic effects on cestode parasite. The study advocates further investigations into the identification of the exact molecules, the precise mode of actions and therapeutic tests, as well as the need for conservation of the rare species of holly.